Surface roughness of titanium disks influences the adhesion, proliferation and differentiation of osteogenic properties derived from human - Frias Martinez, Maria Alejandra (2020)
Purpose The aim of this study was to investigate the response of osteogenic cell lineage and gingival fibroblastic cells to different surface treatments of grade IV commercially pure Titanium (cpTi) disks. Material and methods Grade IV cpTi disks with different surfaces were produced: machined (M), sandblasting (B), sandblasting and acid subtraction (NP), and hydrophilic treatment (ACQ). Surface microtopography characteristics and chemical composition were investigated by scanning electron microscopy (SEM) and energy dispersive x-ray spectrometry (EDS). Adhesion and proliferation of SC-EHAD (human surgically-created early healing alveolar defects) and HGF-1 (human gingival fibroblasts) on Ti disks were investigated at 24 and 48 h, and osteogenic differentiation and mineralization were evaluated by assessing alkaline phosphatase (ALP) activity and alizarin red staining, respectively. Results No significant differences were found among the various surface treatments for all surface roughness parameters, except for skewness of the assessed profile (Rsk) favoring M (p= 0.035 ANOVA). M disks showed a slightly higher (p> 0.05; Kruskal-Wallis/Dunn) adhesion of HGF-1 (89.43 +/- 9.13%) than SC-EHAD cells (57.11 +/- 17.72%). ACQ showed a significantly higher percentage of SC-EHAD (100%) than HGF-1 (69.67 +/- 13.97%) cells adhered at 24 h. SC-EHAD cells expressed increased ALP activity in osteogenic medium at M (213%) and NP (235.04%) surfaces, but higher mineralization activity on ACQ (54.94 +/- 4.80%) at 14 days. Conclusion These findings suggest that surface treatment influences the chemical composition and the adhesion and differentiation of osteogenic cells in vitro.